2008
DOI: 10.1111/j.1751-7117.2008.04628.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Heart Failure Patients' Knowledge, Perceived Barriers, and Attitudes Regarding Low‐Sodium Diet Recommendations to Adherence

Abstract: The purposes of this study were to describe heart failure patient perceptions regarding instructions received for following a low‐sodium diet and the benefits, barriers, and ease and frequency of following the diet. A total of 246 patients with heart failure referred from academic medical centers in the United States and Australia participated in the study. A subset of 145 patients provided 24‐hour urine samples for sodium excretion assessment. While most (80%) patients reported receiving recommendations to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 14 publications
(13 reference statements)
5
38
1
4
Order By: Relevance
“…This value is slightly higher than the 34-40% adherence rate reported by others and may reflect the additional dietary education individual patients received from the research nurse and the reinforcement of this during the home nursing visits. 10,20 Additionally, we found that male sex was a significant risk factor for non-adherence, consistent with prior reports of significantly lower sodium consumption in women. 8, 10,11 Higher BMI was also an independent predictor of non-adherence and may represent worse adherence with sodium or greater total food consumption.…”
Section: Discussionsupporting
confidence: 91%
“…This value is slightly higher than the 34-40% adherence rate reported by others and may reflect the additional dietary education individual patients received from the research nurse and the reinforcement of this during the home nursing visits. 10,20 Additionally, we found that male sex was a significant risk factor for non-adherence, consistent with prior reports of significantly lower sodium consumption in women. 8, 10,11 Higher BMI was also an independent predictor of non-adherence and may represent worse adherence with sodium or greater total food consumption.…”
Section: Discussionsupporting
confidence: 91%
“…In particular, patients identified family and friends as having an impact on nutrition self-care. 62,63 Concordantly, data from Chung et al 4 show that the presence of a spouse, at least in men, impacts adherence to low-sodium diet. Dunbar et al 67 provided an educational intervention with follow-up telephone calls plus 2 additional sessions that focused on developing a family-patient partnership to improve adherence to low-sodium diet.…”
Section: Overweight and Obesitymentioning
confidence: 67%
“…These barriers included lack of awareness of need to limit sodium in diet 3 ; lack of knowledge or ability to identify both lowand high-sodium foods, 3,62 particularly when eating in restaurants 63 ; interference with ability to participate in social (eg, church) events serving food 62 ; lack of food selection 62,63 ; general difficulty following the diet 63 ; no perceived benefit to following the diet 63 ; and friends or family not following the same diet or serving low-salt foods when visiting. 63 Researchers testing interventions to improve adherence to low-sodium diet have used education and skill building to increase awareness of need to limit sodium intake, provide low-salt cooking strategies, improve ability to read sodium content of food labels, and identify low-salt foods in restaurants. 3,64,65 One group of investigators extended their educational intervention to other components of the diet, including dietary fat, protein, and carbohydrate intake.…”
Section: Overweight and Obesitymentioning
confidence: 99%
“…A third subscale (“dependency/restriction”) was identified by Murphy et al;115eoriginal scoring118 recorded only response frequencies of individual items. Abbreviations: √, satisfactory; X, unsatisfactory or incomplete; NR, not reported; NA, not applicable.…”
Section: Figurementioning
confidence: 99%